Characteristics of candidiasis patients and Candida species antifungal sensitivity patterns in tertiary referral hospitals, Indonesia - Grisye Sahetapy; Fidriati Olivia Manongga; Ni Nyoman Sri Budayanti; I Nengah Tony Rustawan (Journal of Clinical Microbiology and Infectious Diseases, 2022)
Introduction: Candida species causes opportunistic infections, such as candidiasis, in patients with compromised immune systems and people receiving long-term antibiotics treatment. The use of antifungals causes resistance. Hence, it is necessary to know the antifungal sensitivity pattern of these organisms, which must be considered in definitive therapy. Therefore, this study aims to determine the characteristics of people with candidiasis and the antifungal sensitivity pattern of Candida species isolates in patients at Prof. Dr. IGNG Ngoerah Hospital, Denpasar, Indonesia. Method: This is a retrospective descriptive study using secondary data from isolates of Candida species that were isolated and identified with the Vitek2® Compact system (bioMérieux, France). The experiment was carried out at the Clinical Microbiology laboratory of Prof. Dr. IGNG Ngoerah Hospital from February 1 to July 30, 2020. Results: A total of 87 Candida species were isolated based on gender, where 55.2% and 44.8% were found in males and females, respectively. Furthermore, the most common isolate was Candida albicans, which accounts for 48.3% of the total microbes. Approximately 41.1% of Candida species were found in the sputum specimens. Furthermore, these species are 100% 98.9% and sensitive to Flucytosine and Micafungin, respectively, while 97.7% and 93.1% sensitivity was recorded for Caspofungin, Voriconazole, Amphotericin B and Fluconazole. Candida species were found in patients with diabetes mellitus and malignancy. They were also observed after using antibiotics for prophylactic, empirical and definitive therapy. Conclusion: The dominant Candida species found was Candida albicans. Characteristics of candidiasis patients were found in people with diabetes mellitus, malignancy and the use of antibiotics in prophylactic, empirical and definitive therapy. Infections caused by these organisms need to be considered in administering antifungal therapy to prevent resistance.